Roadmap for the next decade of plant programmed cell death research - Kacprzyk, Joanna; Burke, Rory; Armengot, Laia; Coppola, Marianna; Tattrie, Sophie B.; Vahldick, Hannah; Bassham, Diane C.; Bosch, Maurice; Brereton, Nicholas J. B.; Cacas, Jean‐Luc; Coll, Núria S.; Gallois, Patrick; et al. (The New phytologist, 2024)
Summary Programmed cell death (PCD) is fundamentally important for plant development, abiotic stress responses and immunity, but our understanding of its regulation remains fragmented. Building a stronger research community is required to accelerate progress in this area through knowledge exchange and constructive debate. In this Viewpoint, we aim to initiate a collective effort to integrate data across a diverse set of experimental models to facilitate characterisation of the fundamental mechanisms underlying plant PCD and ultimately aid the development of a new plant cell death classification system in the future. We also put forward our vision for the next decade of plant PCD research stemming from discussions held during the 31st New Phytologist workshop, ‘The Life and Death Decisions of Plant Cells’ that took place at University College Dublin in Ireland (14–15 June 2023). We convey the key areas of significant progress and possible future research directions identified, including resolving the spatiotemporal control of cell death, isolation of its molecular and genetic regulators, and harnessing technical advances for studying PCD events in plants. Further, we review the breadth of potential impacts of plant PCD research and highlight the promising new applications of findings from this dynamically evolving field.